R-R interval variation and the sympathetic skin response in the assessment of the autonomic nervous system in leprosy patients - Ulvi, H; Yoldas, T; Yigiter, R; Müngen, B (Wiley, 2003)
Objectives - The aim of this study was to evaluate possible autonomic nervous system (ANS) dysfunction in leprosy patients with the sympathetic skin response (SSR) and the heart rate (R-R) interval variation (RRIV) measurements which are easy and reliable methods for evaluation of autonomic functions. Material and methods - We studied 37 lepromatous leprosy patients (mean age: 38 +/- 17 years, range 23-62 years, 20 females and 17 males) and 35 age-matched healthy subjects (mean age: 34.19 +/- 12.74 years, range 24-48 years, 20 females and 15 males). Non-invasive bedside tests (orthostatic test, Valsalva ratio), R-R interval variation (RRIV) during at rest and deep breathing, the SSR latency and amplitude from both palms, and nerve conduction parameters were studied in all the subjects. Results - The mean values of RRIV in leprosy patients during at rest [mean RRIV in patients, 17.42 +/- 8.64% vs controls, 22.71 +/- 3.77% (P < 0.05)] and during deep breathing [mean RRIV in patients, 21.64 +/- 9.08% vs controls, 30.70 +/- 5.99% (P < 0.005)] was significantly lower compared with the controls. The mean latency of SSR in leprosy patients [mean SSR latency in patients, 1.72 +/- 1.13 ms vs controls, 1.30 +/- 0.41 ms (P < 0.05)] was significantly prolonged compared with the controls. The mean amplitude of SSR in leprosy patients [mean SSR amplitude in patients, 0.54 +/- 0.57 muV vs controls, 1.02 +/- 0.56 muV (P > 0.05)] was smaller compared with the controls, but this difference was not significant. The mean Valsalva ratio in leprosy patients [mean in patients, 1.11 +/- 0.13 vs controls, 1.16 +/- 0.07 (P > 0.05)] was smaller compared with the controls, but not statistically significant. The mean difference of systolic and diastolic blood pressure between supine rest and during standing in leprosy patients were higher compared with the controls [mean systolic pressure in patients, 7 +/- 6 mmHg vs controls, 6 +/- 8 mmHg (P > 0.05) and mean diastolic pressure in patients, 3 +/- 3 mmHg vs controls, 3 +/- 2 mmHg (P > 0.05)], but they did not reach statistical significance. Furthermore, lower RRIV and the prolonged SSR latencies in leprosy patients were closely correlated to some parameters of sensorimotor nerve conduction and each other [median nerve distal latency and RRIV, r =-0.67 (P < 0.05), ulnar nerve distal latency and RRIV, r =-0.59 (P < 0.05), RRIV and SSR latency, r =-0.33 (P < 0.02)]. These data indicate that leprosy patients have the functional abnormalities of ANS. Conclusion - We conclude that combined use of these two tests, both of which can be easily and rapidly performed in the electromyogram (EMG) laboratory using standard equipment, allows separate testing of parasympathetic and sympathetic function, and are very sensitive methods in assessing of ANS function in peripheral neuropathy in leprosy patients.
Keywords: leprosy; autonomic nervous system; R-R interval variation; sympathetic skin response